Effect on Satisfactory Seizure Control and Heart Rate Variability of Thread-Embedding Acupuncture for Drug-Resistant Epilepsy: A Patient-Assessor Blinded, Randomized Controlled Trial - Van-Dan Nguyen; Duc-Thang Pham; Minh-An Thuy Le; Guo-Ming Shen (Behavioural Neurology)
This randomized controlled trial investigates the efficacy of thread-embedding acupuncture (TEA) compared to sham TEA in treating drug-resistant epilepsy (DRE). Fifty-four DRE outpatients were randomly divided into two groups: TEA (27 patients) and sham TEA (27 patients). Both groups received four sessions of TEA or sham TEA, spaced four weeks apart, targeting GV20, GV14, BL15, BL18, ST40, and GB34 acupoints. Antiseizure medications were maintained at consistent doses throughout the study. Outcome measures included satisfactory seizure control, seizure freedom, and heart rate (HR) and heart rate variability (HRV) measurements. TEA demonstrated a significantly higher rate of satisfactory seizure control at follow-up compared to the sham TEA group (37% vs. 3.7%, p=0.003). While no significant intergroup differences were observed in HR, HRV, and HRV components at each stage, the TEA group experienced a significant decrease in HR and a significant increase in HRV posttreatment. This study demonstrates TEA’s effectiveness in managing DRE and suggests its impact may relate to heightened parasympathetic nerve activity. Further research with extended follow-up periods is necessary to validate these findings.